Authentic or not? Art historian's reflections on castle reconstructions in contemporary Poland - Lukasz Mikolaj Sadowski (Ochrona Dziedzictwa Kulturowego)
In Poland, most castles were destroyed as early as the 17th and 18th centuries as a result of numerous wars. In the following centuries, an unfavourable political situation or just economic considerations caused numerous demolitions. A significant number of castles disappeared, or functioned as ‘romantic ruins’. A few important castles were rebuilt in the 19th century, in the spirit of ‘historical revival’. In the 20th century, many of the most important buildings  were rebuilt or even reconstructed from scratch. In most cases, the sites were rebuilt immediately after the end of the war, by people who knew the buildings from autopsy, before demolishion.